2019
DOI: 10.1038/s41598-019-44867-z
|View full text |Cite
|
Sign up to set email alerts
|

Inverted U-shaped response of a standardized extract of Centella asiatica (ECa 233) on memory enhancement

Abstract: The herb Centella asiatica has long been considered a memory tonic. A recent review found no strong evidence for improvement of cognitive function, suggesting negative results were due to limitations in dose, standardization and product variation. We used a standardized extract of C. asiatica (ECa 233) to study behavioral, cellular and molecular effects on learning and memory enhancement. ECa 233 (10, 30, and 100 mg/kg) was given orally to normal rats twice a day for 30 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 37 publications
(48 reference statements)
5
21
0
Order By: Relevance
“…Our results suggest that triterpenes may be mostly responsible for the effects observed on cognitive performance; however, a quantitative analysis by LC-MS/MS performed on the whole brain only detected very low amount of madecassic and asiatic acids, very close to the limit of detection, whereas the corresponding glycosides were absent. Our findings are in accordance with a previous study [42], whereas contrasting results have been reported by other authors who have demonstrated the presence of asiaticoside and madecassoside in the hippocampi of rats that were treated with a standardized extract of C. asiatica [37]. Discrepancies could be due to several conditions, such as the dose, length of treatment, formulation, and composition of the phytocomplex.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results suggest that triterpenes may be mostly responsible for the effects observed on cognitive performance; however, a quantitative analysis by LC-MS/MS performed on the whole brain only detected very low amount of madecassic and asiatic acids, very close to the limit of detection, whereas the corresponding glycosides were absent. Our findings are in accordance with a previous study [42], whereas contrasting results have been reported by other authors who have demonstrated the presence of asiaticoside and madecassoside in the hippocampi of rats that were treated with a standardized extract of C. asiatica [37]. Discrepancies could be due to several conditions, such as the dose, length of treatment, formulation, and composition of the phytocomplex.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, we demonstrated that chronic treatment with the higher dose of C. asiatica L. improved cognitive performance. On the contrary, it has been demonstrated that C. asiatica L. induces memory enhancement at the doses of 10 and 30 mg/kg, but it does not do so at 100 mg/kg [37]. This discrepancy could be due to the different extracts or the lengths of treatment.…”
Section: Discussionmentioning
confidence: 95%
“…The concentration of this factor is reduced in the brain of patients with neurodegenerative diseases (Lima Giacobbo et al, 2019). C. asiatica extract, asiatic acid, and (Gopi and Arambakkam Janardhanam, 2017;Nataraj et al, 2017b;Chintapanti et al, 2018;Boondam et al, 2019). C. asiatica and its triterpenoids affect neurological diseases possibly through the mitogen-activated protein kinase (MAPK) signaling pathway, phosphotidylinositol 3 kinase/protein kinase B/ mammalian target of rapamycin (PI3K/Akt/mTOR)signaling pathway, and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) signaling pathway ( Table 2).…”
Section: Effects On Neurological Diseasesmentioning
confidence: 99%
“…In China, it has been a long history of therapeutic uses, e.g., dampness-heat jaundice, heat stroke diarrhea, wound healing 1 4 . In recent years, its extracts and bioactive components have been reported to have anti-inflammatory 5 , anti-tumor 6 , 7 , anti-oxidant 8 , wound healing 9 , cardioprotective 10 and improving-memory effect 11 , 12 . Triterpenes are considered to be the major active components in C. asiatica , such as asiatic acid, madecassic acid, asiaticoside, madecassoside and asiaticoside B 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%